Training Empowers Facilitators to Enhance Vendor Business School Curriculum Understanding and Implementation - CGIAR Initiative on Resilient Cities (CGIAR Initiative on Resilient Cities, 2024)
In an objective to strengthen the delivery of the Vendor Business School (VBS) program, comprehensive training was conducted to address key objectives aimed at refining the facilitators’ skills and strategies. The activity was held on January 17-19, 2024 at the Business Permits and Licensing Office of the Market Development and Administration Department (MDAD). This training brought together enthusiastic facilitators from MDAD, the Small Business and Cooperatives Development and Promotions Office, and Food Security Task Force committed to providing an enriching VBS experience for vegetable vendors in Quezon City. The first objective of the workshop was to ensure that participants delved deeper into the revised VBS curriculum. To reinforce their understanding, facilitators actively participated in teach-back and coaching sessions of the modules. The interactive sessions aimed to equip the facilitators with the knowledge needed to effectively communicate the content to the vendors attending the Vendor Business School. It also provided a platform for them to practice and refine their delivery techniques. The resource persons and other facilitators provided constructive feedback, fostering a learning environment that aimed to enhance each facilitator’s ability to convey the lessons effectively.